Parasitological Survey of Schoolchildren from a High-Altitude Community from Tucumán Province, Argentina. Remarkable Low Detection of Soil-Transmitted Helminths in Comparison with Coastal Communities - Dib, Julian Rafael (2015)
The prevalence of intestinal parasitic infections among schoolchildren in Colalao del Valle, a high-altitude community in Tucumán province, Argentina, was investigated. The data revealed a high prevalence of parasitism (79.7%) with no significant differences in distribution by sex or age. Protozoa infections were the most common with Blastocystis hominis being the most prevalent (62.5%), followed by Giardia lamblia (29.7%), Endolimax nana (15.6%), Entamoeba coli (12.5%) and Iodamoeba bustchili (3.1%). Interestingly, there was an absence of soil-transmitted helminths among the studied population which could be related to climate (variable temperatures, moderate rainfall) and soil type (clay).